Sustainability Assessment of Savings System in Russia - V. V. Litvin; V. V. Maslennikov; N. A. Amosova (Финансы: теория и практика)
Resource and financial support for economic growth is the most important economic task that requires an instant solution. A study of nature, institutional structure, efficiency and sustainability of the savings system in Russia may contribute to this solution and is defined as the subject of this research. The aim of the article is to test the methodology for the sustainability assessment of the savings system in Russia. The methods of system analysis and mathematical statistics represent the methodological basis of the research. The fundamental nature and consistent development of savings relations and processes for the economy provided the starting point of the study The authors consider national savings as an investment resource, which is formed through the institutional structure of the national savings system and the instrumental environment, and their sufficiency ensures stable economic growth of the country. The central point of the research within the framework of the article is the analysis of the intermediary function of the savings system, which optimizes the main parameters of the savings market - the demand for savings resources and their supply, and well as their financial stability assessment The main result of the study provides further development of the previous approach to understanding the essence of the system of national savings (NSS) and its sustainability assessment, in terms of the economic security of the country as well. In addition, the authors attempted to assess the stability limits of the national savings system using mathematical statistics tools. The subject area of the article and the results of the study provide new knowledge about the nature, conditions and sustainability assessments of national savings systems and significantly contribute to the scientific discussion of the current and future trends of the world economy development and economic growth supported by finances and resources.